Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ecy.1621
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal status helps explain invasion success of alien plant species

Abstract: It is still debated whether alien plants benefit from being mycorrhizal, or if engaging in the symbiosis constrains their establishment and spread in new regions. We analyzed the association between mycorrhizal status of alien plant species in Germany and their invasion success. We compared whether the representation of species with different mycorrhizal status (obligate, facultative, or non-mycorrhizal) differed at several stages of the invasion process. We used generalized linear models to explain the occupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 86 publications
4
78
0
1
Order By: Relevance
“…Menzel et al (2018) assessed the relationship between area of occupancy in Germany and two variables: plant species origin (natives; archaeophytes-alien species introduced before the year 1500; and neophytes-alien species introduced after the year 1500) and AM status (obligate, facultative, and non-mycorrhizal). In another regional study, Menzel et al (2017) reported that the mycorrhizal status significantly explained the occupied range of alien plants, with facultative mycorrhizal species inhabiting a larger range than non-mycorrhizal species, while obligate mycorrhizal plant species were intermediate. These authors also showed that while in neophytes with facultative mycorrhizal associations there are trade-offs between plant retention of the mycorrhizal symbiosis and allocation of C to the development of other plant structures, such trade-offs were almost absent among natives (Menzel et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Menzel et al (2018) assessed the relationship between area of occupancy in Germany and two variables: plant species origin (natives; archaeophytes-alien species introduced before the year 1500; and neophytes-alien species introduced after the year 1500) and AM status (obligate, facultative, and non-mycorrhizal). In another regional study, Menzel et al (2017) reported that the mycorrhizal status significantly explained the occupied range of alien plants, with facultative mycorrhizal species inhabiting a larger range than non-mycorrhizal species, while obligate mycorrhizal plant species were intermediate. These authors also showed that while in neophytes with facultative mycorrhizal associations there are trade-offs between plant retention of the mycorrhizal symbiosis and allocation of C to the development of other plant structures, such trade-offs were almost absent among natives (Menzel et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…They found that AM status significantly explained the area of occupancy of natives and neophytes, with facultative mycorrhizal plant species occupying larger areas in both groupsthis corresponds to our finding reported above. This mycorrhizal status is especially advantageous for successful spread of alien plants, as the flexibility of being facultatively mycorrhizal allows plants to explore a broader set of ecological strategies (Menzel et al 2017). This indicates that natives and neophytes benefit differently from mycorrhizal symbiosis and suggests that native AM fungal partners might be less important for neophytes than for native plant species, or that more time of co-evolutionary experience is required to establish similar relationships between neophytes and native fungal symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Menzel et al . () found that nonmycorrhizal alien species are not more widely spread than obligate mycorrhizal alien species in Europe. Menzel et al .…”
Section: Simplification Of Complex Network Into Interaction Motifsmentioning
confidence: 99%
“…Menzel et al . () suggested that facultative mycorrhizal species may actually be more widely spread than either obligate arbuscular or nonmycorrhizal plants, but the analysis of facultative species has to be treated with caution as more frequently observed species are more likely to be classified as facultative in their database (at the extreme, a species with only one observation of presence or absence of mycorrhizas cannot be considered facultative in that analysis; T. Kuyper, pers. comm.…”
Section: Simplification Of Complex Network Into Interaction Motifsmentioning
confidence: 99%
“…Due to relatively low host specificity of AM symbioses, AM fungi can form symbiotic associations with invasive species in nonnative habitats even though they lack a co‐evolutionary history with these new hosts (Moora et al , ; Dickie et al , ). Interactions between plants and AM fungi may enhance species invasiveness by facilitating the establishment, persistence and dominance of invasive plants in new habitats (Pringle et al , ; Menzel et al , ). Previous studies showed that carbon and mineral nutrients can be transferred from native plants to invasive plants via common mycorrhizal networks (Carey et al , ; Awaydul et al , ).…”
Section: Introductionmentioning
confidence: 99%